Using the theory of planned behavior to predict condom use among men who have sex with men in upper Northern Thailand - Sunanta, Montiwa; Chautrakarn, Sineenart; Ong-artborirak, Parichat (Journal of Medical and Public Health Region 4, 2024)
This study was Cross-sectional analytic study which has objective to study the between Theory of Planed Behavior (TPB) to predicted Condom use behavior among Men who have sex with men (MSM) in Northern Thailand. Sample were 342 cases who recruited by convenience sampling and Snow ball sampling techniques. Data were collected by questionnaires, which developed from TPB, there was Index of item objective congruence (OIC) 0.6 - 1 point and was reliability tested by Cronbach’s alpha coefficient = 0.82. Using descriptive statistics to explained sampling’s characteristics, the TPB correlation with Condom use was analyzed by Spearman’s rank correlation coefficiency and was predicted condom use possibility by Logistic regression model. This research results were following: Sample were 27.9 and consistently using a condom 49.7%. The result was related with TPB model, Condom use intention was significant correlation with Condom use intention (r = 0.6, p-value < 0.001). The TPB was 36% predicted intention of condom use (R2 = 0.36) and was 21% predicted condom use behavior (R2 = 0.21). The people who are involved Condom use promotion/policy should develop behavior modification program which heading to reinforce condom use behavior intention than condom use knowledge.